(untitled) (KULT_online, 2017)
In Fast Forward. The Future(s) of the Cinematic Arts, Holly Willis charts an extensive overview of contemporary cinematic art in all its diversity. Analyzing artworks ranging from websites and apps to conventional fiction films, she is able to connect the current ‘post-cinematic’ moment to a decided shift towards posthumanism. To do so, she explores the different aspects – technological, aesthetic, and practical – of an increasingly decentered cinematic universe, identifying the posthuman perspectives and techniques prevalent in the artworks she considers.